Pumpkin seed oil-loaded chitosan nanoparticles enhance growth, digestive enzymes, and immune response in whiteleg shrimp (Litopenaeus vannamei): Impacts on histopathology and survival against Vibrio parahaemolyticus - El-Sayed Hemdan Eissa; Wesam Mohamed Salama; Samia Elbahnaswy; Mai A.M. El-Son; Zienab E. Eldin; Sara Amer; Layla A. Almutairi; Fatma Mohamed Ameen Khalil; Safia M.A. Bahshwan; Mada M. AL-Qurashi; Yasmin M. Abd El-Aziz; Moaheda E.H. Eissa; et al. (Aquaculture Reports)
The research evaluated the innovative effects of pumpkin seed oil-loaded chitosan nanoparticles (ChNPs/PSO) on the growth, body composition, digestive enzymes, immune response, organ histopathology, and survivability of whiteleg shrimp (Litopenaeus vannamei) juveniles against Vibrio parahaemolyticus. Shrimp were fed basal diets (control diets and 1 g of free nano chitosan; ChNPs) supplemented with ChNPs and different levels of ChNPs/PSO at 1 (ChNPs+PSO1), 1.5 (ChNPs+PSO1.5), and 2 (ChNPs+PSO2) mL/kg for a continuous 60 days period. At the end of the feeding trial, shrimp juveniles were exposed to V. parahaemolyticus. The results showed that dietary inclusion of ChNPs/PSO (1.5 or 2 mL) significantly improved the final weight, feed conversion ratio, weight gain, and specific growth rate of shrimp compared to other groups (P < 0.05). Shrimp fed diets supplemented with 1.5 or 2 mL of ChNPs/PSO demonstrated significantly higher survival rates compared to other groups. These groups also exhibited significant increases in crude protein, ash content, phagocytic index, superoxide dismutase, and lipase levels (P < 0.05). The ChNPs+PSO2 group showed the highest amylase activity (P < 0.05). Furthermore, shrimp in these groups displayed significantly elevated total hemocyte counts, lysozyme activity, and bactericidal capacity (P < 0.05). Besides, a significant increase in phenoloxidase and phagocytic activities was observed in the ChNPs+PSO1 group (P < 0.05). The expression levels of prophenoloxidase (LvproPO) and hemocyanin (LvHc) genes were significantly increased in the hepatopancreas of shrimp fed diets enriched with 1.5 or 2 mL of ChNPs/PSO. The survival rate after infection with V. parahaemolyticus was higher in all ChNPs/PSO-enriched groups compared to the control group. Dietary supplementation with ChNPs/PSO restored the histological damages in the muscle, hepatopancreas, and intestine induced by V. parahaemolyticus infection. In summary, pumpkin seed oil-loaded chitosan nanoparticles (ChNPs/PSO) hold potential as a feed additive for enhancing growth performance, immune ability, and disease resistance against V. parahaemolyticus in Whiteleg shrimp.